Seminar on “Globalisation and Internationalisation of Higher Education in Malaysia: The Book Project” - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Concerned about the interchangeably improper use of the terms ‘globalisation’ and ‘internationalisation’ within the realm of Malaysian higher education, t he National Higher Education Research Institute (IPPTN) together with the Ministry of Higher Education Malaysia organised a one-day seminar on “Globalisation and Internationalisation of Higher Education in Malaysia (GIHE): The Book Project”.